2010
DOI: 10.3171/2009.8.peds09117
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous choroid plexus carcinoma and pilocytic astrocytoma in a pediatric patient

Abstract: Simultaneous primary brain tumors in pediatric patients without prior chemotherapy or radiotherapy, phacomatosis, or known familial history are a rare occurrence. The authors report the case of a 4-year-old boy with simultaneous choroid plexus carcinoma and pilocytic astrocytoma with features of oligodendroglioma. Magnetic resonance imaging studies revealed diffuse heterogeneously enhancing left intraventricular and posterior fossa tumors initially believed most consistent with multicentric choroid ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
2
0
2
Order By: Relevance
“…12,13 In pediatric patients, multicentric glioma are even rarer and limited to only few case reports. 1416 A genetic predisposition such as neurofibromatosis or Li-Fraumeni syndrome in which brain tumors occur frequently is unlikely in this case, as an unremarkable family history and the absence of any clinical symptoms suspicious of these diseases argue against this possibility.…”
Section: Discussionmentioning
confidence: 90%
“…12,13 In pediatric patients, multicentric glioma are even rarer and limited to only few case reports. 1416 A genetic predisposition such as neurofibromatosis or Li-Fraumeni syndrome in which brain tumors occur frequently is unlikely in this case, as an unremarkable family history and the absence of any clinical symptoms suspicious of these diseases argue against this possibility.…”
Section: Discussionmentioning
confidence: 90%
“…Gelabert et al reported the simultaneous occurrence of a frontal lobe astrocytoma and a colloid cyst of the third ventricle, both derived from displaced primitive neuroectodermal cells, suggesting the role of a single oncogenic factor in producing different tumors in the same individual [19]. Another hypothesis suggested by Karami et al explains that this phenomenon of simultaneous occurrence of histologically different tumors in different or same areas of the brain could be purely coincidental [20].…”
Section: Discussionmentioning
confidence: 99%
“…Santral sinir sisteminin farklı anatomik bölgelerinde kombine patolojilerin ortaya çıkması enderdir ve birbirine eşlik eden tümörlere bakıldığında, literatürde genellikle meningiomalar ve gliomaların birlikteliği yer almaktadır (5) . Bunlara kıyasla, ventriküler sistemde eşlik eden bir tümörün olması oldukça ender görülmektedir (6) .…”
Section: Discussionunclassified
“…Farklı histopatogenezdeki multipl beyin tümörlerinin ortaya çıkması tamamen rastlantısal olabilir, ama bu konuyu açıklamaya yönelik hipotezler de ortaya atılmıştır. Bunlardan ilki, "local cross-talk" teorisi olarak bilinen, önemli sayıda olgu sunumuyla ele alınan sav, bir tümörün lokal proliferasyon oluşturması ve diğer bir tümörü meydana getirmede irritan ajan olarak davranması olasıdır (6) . Yine, kolloid kist ve glioma birlikteliği olan olgularda, tümörlerin primitif nöroektodermal hücrelerden ve dolayısıyla multipotensiyel hücrelerden kaynaklanması nedeniyle farklı bölgelerde olmalarına rağmen, aynı onkojene maruz kalmaları sonucu gelişmiş olabileceği iddia edilmiştir (1) .…”
Section: Discussionunclassified